Influence of Preliminary Deformation on Micromechanisms of Failure of Offshore Gas Pipeline Material; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Maruschak P.; Danyliuk I.; Poberezhnyi L.; Pyrig T.; Panin S. V. Sergey Viktorovich (Materials Science in Mechanical Engineering, 2015)
Title screen